2012
DOI: 10.1016/j.bbcan.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic role and therapeutic target of leptin signaling in breast cancer and cancer stem cells

Abstract: Significant correlations between obesity and incidence of various cancers have been reported. Obesity, considered a mild inflammatory process, is characterized by a high level of secretion of several cytokines from adipose tissue. These molecules have disparate effects, which could be relevant to cancer development. Among the inflammatory molecules, leptin, mainly produced by adipose tissue and overexpressed with its receptor (Ob-R) in cancer cells is the most studied adipokine. Mutations of leptin or Ob-R gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(162 citation statements)
references
References 253 publications
(342 reference statements)
2
159
0
1
Order By: Relevance
“…36, 37 Adipocytes secrete leptin and other adipokines, and leptin concentration is positively correlated with total adipose tissue. 38 Although it can be challenging to separate the effects of leptin from other adipokines, some studies have shown leptin levels to have independent prognostic effects on breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…36, 37 Adipocytes secrete leptin and other adipokines, and leptin concentration is positively correlated with total adipose tissue. 38 Although it can be challenging to separate the effects of leptin from other adipokines, some studies have shown leptin levels to have independent prognostic effects on breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, increases in leptin both induce aromatase-mediated estrogen production and transactivate ER signaling in MCF7 breast cancer cells, as well as stimulate leukocyte secretion of IL-1, IL-6, IL-12, TNFα, IFNγ, and nitric oxide, which may create a regulatory feedback cascade to promote tumor growth and leukocyte invasion. Leptin can also increase tumor production of several proangiogenic factors, including MMP-2, MMP-9, and VEGF, although leptin has itself been reported to promote angiogenesis through actions on VEGF receptor signaling and Notch expression (101,102). Finally, recent studies suggest that leptin may promote breast cancer epithelial-mesenchymal transition and cancer stem cell renewal (101,103).…”
Section: Adipokines and Cytokinesmentioning
confidence: 92%
“…Binding to the specific receptors (Ob-R) is essential for leptin to execute its biological functions (23). Western blot and Immunofluorescence assay were performed to examine the expression of of ObR, Leptin and IL-8 in invasive breast carcinoma without axillary lymph node metastases was lower than those in LNM,and higher than those in benign breast tissue.…”
Section: Leptin Induced Epithelial-mesenchymal Transition Of Breast Cmentioning
confidence: 99%